2015
DOI: 10.3758/s13420-015-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of test context in latent inhibition of conditioned inhibition: Part of a search for general principles of associative interference

Abstract: Two lick-suppression experiments with rats assessed interference with behavior indicative of conditioned inhibition by a latent inhibition treatment as a function of test context. We asked what effect the test context has, given identical latent inhibition treatment in Phase 1 and identical conditioned inhibition training in Phase 2. In Experiment 1, an AAA vs. AAB context-shift design determined that latent inhibition treatment in Phase 1 attenuated behavior indicative of conditioned inhibition training admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(108 reference statements)
2
5
0
Order By: Relevance
“…Moreover, when testing conditioned inhibition outside from the context within which latent inhibition operations were carried out, the effects of latent inhibition waned. Together, the findings of Miguez et al (2015) support the idea that latent inhibition effects can be better understood as interference upon performance rather than upon learning.…”
Section: Recent Advancessupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, when testing conditioned inhibition outside from the context within which latent inhibition operations were carried out, the effects of latent inhibition waned. Together, the findings of Miguez et al (2015) support the idea that latent inhibition effects can be better understood as interference upon performance rather than upon learning.…”
Section: Recent Advancessupporting
confidence: 57%
“…In another study, Miguez, Soares, and Miller (2015), after demonstrating that conditioned inhibition effects could be attenuated by prior latent inhibition operations, sought to inquire whether this phenomenon was context-specific. Using a conditioned suppression paradigm, these authors observed that when latent inhibition and feature-negative discrimination operations were conducted in different contexts, the interference of the former upon the latter was disrupted.…”
Section: Recent Advancesmentioning
confidence: 99%
“…As previously stated, this finding challenges accounts of LI and CI that posit that the observed retardation in development of stimulus control by the target cue is due to a failure to learn (e.g., the view that LI training decreases attention to the target cue, thereby retarding excitatory acquisition per se). Along with other reports (e.g., Miguez, Soares, & Miller, 2015), the present experiments indicate that the associative interference that produces retarded acquisition of behavioral control is due to conflict at test between memories of the two training experiences, not the product of an acquisition or retention deficit.…”
Section: Discussionsupporting
confidence: 88%
“…Studies in animals suggest that LI is context-dependent. Specifically, the LI effect is attenuated or abolished when the context in which the CS was presented changes between pre-exposure and conditioning ( Hall and Channell 1985 ; Escobar et al 2002 ; Quintero et al 2011a , b ; Miguez et al 2015 , 2018 ; Miller et al 2015 ). Shifts in temporal contexts have also been shown to modulate the magnitude of LI ( Manrique et al 2004 ; Molero et al 2005 ).…”
Section: Variables Impacting LImentioning
confidence: 99%